pH-dependent oxacillin tolerance of Staphylococcus aureus. - Venglarcik, J S (1983)
A proportion of clinical isolates of Staphylococcus aureus exhibit resistance to bactericidal activity of certain antibiotics, despite normal susceptibility to inhibition. This phenomenon is termed "tolerance." The methodology used to determine tolerance varies greatly. To clarify the relationship between laboratory methodology and tolerance, we determined the minimal bactericidal concentrations and minimal inhibitory concentrations for 20 clinical isolates by two methods. Inocula were prepared by either 3-h growth of the organism in Mueller-Hinton broth or overnight (22 to 24 h) cultures in Trypticase soy broth (BBL Microbiology Systems, Cockeysville, Md.). All inocula were plated for colony counts and tested for pH. An American Type Culture Collection (Rockville, Md.) reference strain was included in all tests for standardization. Tolerance was defined by the strictest criterion, i.e., a minimal bactericidal concentration/minimal inhibitory concentration ratio of greater than or equal to 100. With the first method, none of the 20 isolates displayed tolerance (mean inoculum pH, 7.15). When inocula were grown in Trypticase soy broth with overnight incubation, 35% (7 of 20) showed tolerance (mean inoculum pH, 6.22). There was a significant association between the decreased bactericidal capacity at high oxacillin concentrations and overnight incubation in Trypticase soy broth (P less than 0.01). We suggest that tolerance in staphylococci is in some way related to the pH value of the inoculating culture. Such pH-induced tolerance may have a clinical corollary in sequestered infections where the pH is acidic.